Climate Diplomacy: Viability of Pakistan-India Cooperation - Sadeer Ahmad (CISS Insight Journal, 2024)
Climate change is a global phenomenon and poses a formidable challenge for developed and developing countries. Climate-related disasters can contribute to economic and political instability. Climate change is affecting South Asia in myriad ways and is a common challenge that Pakistan and India can mutually meet to ensure their sustainable development. Joint efforts in renewable energy, water resource management, agriculture and food security, disaster risk reduction, and air pollution are possible. This paper examines the potential for climate diplomacy in South Asia and assesses the feasibility of Pakistan-India cooperation on climate change. It underscores the significance of establishing a bilateral climate framework, engaging in joint disaster relief operations, collaborating on green energy initiatives, exploring climate finance options, and facilitating joint research and training programs. By leveraging shared vulnerabilities, past cooperation experiences, and regional and global commitments, they can, among other things, collaborate on the diplomatic front to combat climate change and enhance climate resilience in the South Asian region.